The efficacy and safety of patient-controlled intravenous analgesia with esketamine after total hip arthroplasty: a randomized controlled trial - Song Qu; Wen-Jie Zhang; Hai-Jiao Zhou; Fei Deng; Rui-Juan Liu; Wen-Jun Yan (BMC Anesthesiology)
Abstract Purpose To evaluate the efficacy and safety of esketamine-based patient-controlled intravenous analgesia following total hip arthroplasty. Methods A total of 135 total hip arthroplasty patients were randomly assigned to one of the three treatment groups: esketamine, sufentanil or continuous fascia iliaca compartment block (FICB) group. The primary endpoint was the postoperative visual analogue scale (VAS) pain scores at rest and on movement. Secondary endpoints included preoperative 1-day and postoperative 7-day Self-Rating Anxiety Scale (SAS) and Self-Rating Depression Scale (SDS) scores, the satisfaction of patients and surgeons, postoperative 1-month and 3-month Harris function scores, the incidence of adverse reactions. Results At 48 h post-surgery, the VAS pain scores in the esketamine and FICB groups at rest and on movement were significantly lower than those in the sufentanil group (P < 0.05). The satisfaction of patients in the esketamine group was higher than that in the sufentanil and FICB groups (P = 0.014). The satisfaction of surgeons in the esketamine and FICB groups was higher than that in the sufentanil group (P = 0.002). At postoperative day 7, the SAS scores and SDS scores in the esketamine group were significantly lower than those in the sufentanil and FICB groups (P < 0.05). Compared with the sufentanil group, the postoperative nausea and vomiting, dizziness and total adverse reactions in the esketamine group and FICB group were lower (P < 0.05). Conclusion Patient-controlled intravenous analgesia with esketamine has the potential to provide good postoperative analgesia for total hip arthroplasty patients, reduce the incidence of adverse reactions after the operation, improve the satisfaction of patients and surgeons, and significantly improve patients’ postoperative mood. Trial registration : ChiCTR2300069632 ( https://www.chictr.org.cn/ ) (March 22th, 2023).